Faktor Penyebab Ketidakakuratan Kode Diagnosis Penyakit Pasien Rawat Inap Di Rumah Sakit X - SURYANDARI, ENDANG SRI DEWI HASTUTI; Setyawati, Fitri Eka; Gunawan; Sangkot, Hartaty Sarma; Wijaya, Avid (Jurnal Kesehatan Qamarul Huda, 2024)
The activity of coding disease diagnosis was an important activity for preparing internal and external hospital reports, planning and managing hospitals and determining hospital service rates. Based on observations of 10 files samples from inpatients at Hospital X, 2 files were found with inaccurate disease codes (20%). The aim of the research was to identify factors that cause inaccurate disease codes for patients treated at RS X. The research method used a mixed method with retrospective approach by combined quantitative and qualitative research. The sample analyzed were 100 files inpatients for the period December 2022 using a simple random sampling by lottery and 2 coders as respondents. The results showed that 82% of the diagnosis codes were accurate and 18% of the diagnosis codes were inaccurate. The factors causing inaccurate diagnosis codes at Hospital X were lack of knowledge in coding and 1 officer had never attended coding training (man factor); lack of socialization of coding SOPs which contain explanations of the use of ICD 10 as a reference in codification (method factor); there was no ICD 10 Volume 2 version for 2010 (material factor); and lack of financial support for coding training activities for officers and procurement of ICD 10 volume 2 version for 2010 (money factor). There was a need to increase knowledge and skills in codification through coding training activities for officers, carrying out revisions and socialization regarding coding SOPs and procurement of ICD 10 volume 2 to increase the accuracy of diagnosis codes.